FAILURE TO MEET GENERATIVE SELF-EXPECTATIONS TIED TO HEALTH AND WELL-BEING THROUGH COGNITIVE-AFFECTIVE STATES. (11th November 2018) - Grossman, M; Gruenewald, T
Abstract: Generativity, or concern with contributing to the welfare of others, is theorized to be an important focus of middle-to-later life. Generative feelings and behaviors are associated with countless health and well-being benefits. This study examined how failure to meet generative self-expectations with age is linked to cognitive-affective states (social connectedness, self-worth, and positive affect), and consequently, life satisfaction and health. Analyses used data from Waves 2 and 3 of the National Survey of Midlife Development in the United States (MIDUS). Multiple mediation tests assessed whether these cognitive-affective states linked generative failure to poorer life satisfaction and health (mental and physical health, activities of daily living (ADL) limitations, chronic conditions). A Johnson-Neyman moderation analysis examined whether these associations varied with age. Generative failure was significantly associated with lower life satisfaction, and this link was partially mediated by all three cognitive-affective states (p's<0.001). Generative failure was also significantly related to worse mental and physical health and a greater number of ADL limitations and chronic conditions, all partially mediated by positive affect (p<0.001). Generative failure had the most significant impact on health and life satisfaction in individuals ages 44–74. Benefits of generativity may stem in part from the cognitive-affective pathways explored here. Results underscore the importance of facilitating opportunities for generative engagement to support trajectories of successful aging, as defined by satisfaction with life and maintenance of health and function. Such opportunities may have the strongest influence on the health and well-being of those in middle and young-old age groups.